Features of Food Hypersensitivity in Children with Autism Spectrum Disorder - M. I. Khudiakova (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Currently, the incidence of autism spectrum disorders (ASD) continues to increase in the children’s population. However, the pathogenesis of autism remains controversial.The purpose of this work is to evaluate the performance of the elimination nutritional approaches to the dynamics of indicators of food hypersensitivity, the balance of interleukins and psychophysiological parameters in children with ASD.Methods. A prospective cohort study of children aged 7 ± 2 years, healthy and diagnosed with ASD was performed. Determination of specific immunoglobulin concentrations to 111 food antigens and interleukins was measured by ELISA. Psychophysiological indicators of communicative competence in children with ASD were evaluated in the ATEC-test.Results. It was established that in children with ASD (n = 69), the frequency of occurrence of food hypersensitivity and indicators of specific sIgG concentrations to food antigens of dairy and grain products are higher (р < 0.05). A direct correlation was found between the concentration of INFγ, IgG concentrations to antigens of dairy, grain products and C. albicans. High ratios of the INFγ/IL4 and INFγ/IL10 ratios (p < 0.05) were revealed. As a result of compliance with the elimination diet was noted significant decrease in the concentration of sIgG to food antigens, sIgG to C. albicans, changes indicators following the results of ATEC testing.The data obtained revealed the unexplored effects the influence of specific food hypersensitivity on the process of initiation and maintenance of immune inflammation, as well as on the communicative competence in pathological conditions. A personalized elimination diet can improve the immunorehabilitation and the quality of life of children with autism.